New testing device for air permeability - Lilia Sabantina; Andrea (Communications in Development and Assembling of Textile Products)
Air permeability is used to characterize textile fabrics with respect to their usability as a garment or filter, airbag or parachute. It depends on the fabric’s porosity, air voids in the fabric, yarn specifications, thickness and other parameters, making it hard to calculate it reliably from other parameters. At the same time, measuring air permeability requires relatively expensive and complex equipment that cannot simply be built by everybody. Here, we suggest a simple device, which can be built from inexpensive components and correlates air permeability to a time measurement. We show that these values are highly correlated with the results gained by the frequently used standard EN ISO 9237.